Online to Face-to-Face Learning Transition: Its Psychological Effect - Perocillo, Jehan O.; Sumicad, Rulthan P.; Gullegos, Kahlil Mae B.; Repollo, Maria Melessa (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study explores the psychological impact of transitioning from online to face-to-face learning among 2nd-year Psychology students at the University of Cebu – Main Campus during the academic year 2022-2023. The challenges faced during this transition and the participants' lived experiences are discussed. Using qualitative research employing purposive sampling, second-year psychology students were selected for one-on-one interviews. Thematic analysis of transcribed interviews identified 11 emergent themes, categorized into three overarching themes addressing sub-problems. Challenges during the transition were classified under